Sazonalidade e dinâmica de assembleias de plantas aquáticas em lagos rasos no semiárido brasileiro - Farias, Dayse Leone dos Santos (2019)
Aquatic plant assemblages can be organized by several of factors, biotic and abiotic, which influence in different ways depending on the scale of observation and can act simultaneously. Therefore, in this study we aimed: (1) to verify how the biotic interactions were structured during a seasonal cycle, testing the hypothesis that species with greater morphological similarity tend to be excluded due to the asymmetric competition for the resources, predominating the coexistence of hydrophytes with different growth forms that complement each other spatially at all stages of succession; (2) to verify the relationship between sediment changes during a seasonal cycle with interpopulational interactions in aquatic plant assemblages in semi-arid shallow lakes, testing the hypothesis that sediment variation is related to species dominance, allowing for less overlap resources. We observed that competition is the biotic filter that influences the organization of aquatic plants in these environments. And that the coexistence of hydrophytes with higher index of dominance with complementary forms of growth occurred in shallow lakes, but with combinations different from those expected for these environments. The variables depth and turbidity were significantly correlated with the dominance of the species. Besides these variables, the sediment also showed importance in structuring the assemblies, indicating that there is a differentiation in the niche of the species. However, the seasonal variation does not influence structure of the assemblies. Thus, we observe that both biotic and abiotic factors are important factors on aquatic plants.